Reticulitermes malletei (Isoptera: Rhinotermitidae): a valid Nearctic subterranean termite from Eastern North America - Austin, J. W.; Bagnères, A. -G.; Szalanski, A. L.; Scheffrahn, R. H.; Heintschel, B. P.; Messenger, M. T.; Clément, J. -L.; Gold, R. E. (Zootaxa, 2007)
The taxonomic status of Reticulitermes Holmgren in North America has been in need of revision for years, but because of morphological ambiguity, traditional morphological identification of Reticulitermes species has always been difficult and unreliable. Analysis of termites, applying non-morphological genetic comparisons of mitochondrial DNA from numerous populations across North America, has implicated new species which are presently under investigation. Applying the 16S rRNA gene with biometric, cuticular hydrocarbons, and ethological data, a cryptic species of Nearctic Reticulitermes has been identified from Delaware, Georgia, Maryland, North Carolina, and South Carolina and determined to constitute a valid species with an apparently Atlantic distribution. Epicuticular hydrocarbon analysis showing the presence of rare triunsaturated alkenes, and a total absence of methyl branched alkanes also support this cryptic group as a distinct species. The name for this species is Reticulitermes malletei, previously described, but not generally accepted by termite experts in the United States. Comparisons from a 403 bp region of the mtDNA 16S rRNA gene was used to discriminate known Reticulitermes species from North America: The eastern subterranean termite R. flavipes (Kollar), dark southern subterranean termite R. virginicus (Banks), light southern subterranean termite R. hageni Banks, arid subterranean termite R. tibialis Banks, and western subterranean termite R. hesperus Banks. When compared to this new species, both maximum parsimony and maximum likelihood support their genetic isolation from sympatric populations of known species and eliminate either exotic Palearctic introductions or western Nearctic involvement.